Facile in-situ formation of high efficiency nanocarbon supported tungsten carbide nanocatalysts for hydrogen evolution reaction. (16th August 2018) - Liu, Cheng; Wen, Yan; Lin, Liangxu; Zhang, Haijun; Li, Xifei; Zhang, Shaowei
Abstract: Electrochemical hydrogen evolution reaction (HER) is one of the key techniques for hydrogen production. Much great effort has been made so far to develop highly efficient HER catalysts to replace expensive precious metals ( e.g. Pt). Unfortunately, the synthesis processes were generally not cost-effective and/or scalable. So it is highly desirable to develop a facile technique to enhance HER activity of conventional inexpensive but less active materials. In this work, monodispersed tungsten carbide (WC) nanoparticles (<5 nm) were in-situ formed/anchored on nanosized carbon black (CB) and carbon nanotube (CNT) via a simple low temperature molten salt synthesis technique. Owing to this special hybrid structure, both the exposed surface area of active species and the electrical conductivity of the catalysts were increased effectively, making the catalysts perform considerably better in HER than pure WC and WC based catalysts prepared via other conventional routes. WC nanocrystals in-situ formed/anchored on CNTs showed small onset overpotential (90 mV), low Tafel slope (69 mV dec −1 ), high current density (93.4 and 28 mA cm −2 at 200 and 300 mV, respectively) and excellent stability (remaining stable even after 3000 cycles). Such a performance is one of the best among those of WC based electrocatalysts developed to date. We demonstrate here significantly improved HER performances of inexpensive tailored WC materials, along with a facile synthesis strategy which could be also readily extended to prepare a range of other types of mono-dispersed nanocatalysts for more potential applications. Graphical abstract: A feasible and low cost molten salt synthesis technique has been developed to prepare tungsten carbide nanocatalysts which highly dispersed and anchored firmly on nanocarbon black and carbon nanotubes with carbon covering-free. This simple preparation has led to one of the best catalytic performance of hydrogen evolution reaction among tungsten carbide catalysts. Highlights: A novel strategy has been developed to prepare in-situ tungsten carbide nanocrystals. The nanocrystals anchored on nanocarbon substrates are free from impurity covering. Most of mono-dispersed nanocrystals formed (WC coexisting with W2 C) are <5 nm. The nanocatalyst exhibits considerably improved performance in H2 evolution reaction. The performance is one of the best among WC based catalysts reported to date.